Research Progress and Outlook of Molecular Dynamics Simulation on Carbon Dioxide Applied for Methane Exploitation from Hydrates - Qiannan Yu; Chenglong Li; Boyang Peng; Huimin Tang; Tao Yang; Yang Yu; Kun Zhang; Zhijing Chen (Molecules)
Research progress of carbon dioxide applied for methane exploitation from hydrates is summarized, with a focus on advances in molecular dynamics simulations and their application in understanding the mechanism of carbon dioxide replacement for hydrate exploitation. The potential of carbon dioxide in enhancing energy recovery efficiency and promoting carbon capture and storage is emphasized. An overview is provided of the advancements made in utilizing carbon dioxide for methane hydrate exploitation, highlighting its significance. Subsequently, the theoretical foundations and techniques of molecular dynamics simulations are delved into, encompassing key elements such as statistical ensembles, molecular force fields, and numerical solution methods. Through simulations, various characterization parameters including mean square displacement, radial distribution functions, coordination numbers, angular order parameters, and hydrogen bonds are computed and analyzed, which are crucial for understanding the dynamic changes in hydrate structures and the replacement process. Thorough research and analysis have been conducted on the two possible and widely debated mechanisms involved in the replacement of methane hydrates by carbon dioxide, with a particular emphasis on guest molecular replacement and hydrate reconfiguration. These processes encompass the intricate interactions between carbon dioxide molecules and the cage-like structure of hydrates, as well as the rearrangement and stabilization of hydrate structures. Several key issues surrounding the application of carbon dioxide for methane hydrate exploitation are identified, including the influence of thermodynamic conditions, the selection of auxiliary gases, and other potential factors such as geological conditions and fluid properties. Addressing these issues is crucial for optimizing the extraction process and enhancing economic and environmental benefits. A theoretical foundation and technical reference for the application of carbon dioxide in methane hydrate exploitation are provided, while future research directions and priorities are also outlined.